Analytical Spectrometric Study For Determining Dapagliflozin Propanediol Monohydrate Individually Or In Presence Of Metformin Hydrochloride In Tablets Formulation - SAAD ANTAKLI; Raghad Kabbani; and Rama Labban (JOURNAL OF ADVANCES IN CHEMISTRY, 2020)
First simple spectrophotometric method was developed and applied to determine Dapagliflozin Propanediol Monohydrate by Zero Spectrophotometry and First Derivative Spectrophotometric method for determining of Dapagliflozin Propanediol Monohydrate (DAPA) in the presence of Metformin Hydrochloride (MET). Zero spectrophotometric (ZS) was applied for the determination of (DAPA) at 223.5 nm. Linearity range was (2.61– 31.23) µg/mL. Regression analysis showed a good correlation coefficients R2 = 0.9989. The limit of detection (LOD) and limit of quantification (LOQ) were to be 0.569 µg/mL and 1.724 µg/mL, respectively. Derivative spectrophotometric (1DS) was applied for the determination of (DAPA) in the presence (MET). (DAPA) was determined at 233 nm (1D233). Linearity ranges were (5.21 – 41.64) µg/mL for (DAPA). Regression analysis showed a good correlation coefficients R2 = 0.9994. The limit of detection (LOD) and limit of quantification (LOQ) were to be 0.732 µg/mL and 2.218 µg/mL for (DAPA). The proposed Zero spectrophotometry method was applied to analysis individual (DAPA), and the derivative (1D233) method was applied to analysis (DAPA) individually or with (MET) combination in Syrian trademark drugs.